Isotonic saline nasal irrigation in clinical practice: a literature review - Sabrina Costa Lima; Ana Carolina Campos Ferreira; Tereza Cristina da Silva Brant
Abstract Introduction: Nasal instillation of saline solution has been used as part of the treatment of patients with upper respiratory tract diseases. Despite its use for a number of years, factors such as the amount of saline solution to be used, degree of salinity, method and frequency of application have yet to be fully explained. Objective: Review the reported outcomes of saline nasal irrigation in adults with allergic rhinitis, acute or chronic sinusitis and after functional endoscopic sinus surgery (FESS), and provide evidence to assist physiotherapists in decision making in clinical practice. Methods: A search was conducted of the Pubmed and Cochrane Library databases between 2007 and 2014. A combination of the following descriptors was used as a search strategy: nasal irrigation, nasal lavage, rhinitis, sinusitis, saline, saline solution. Results: Eight clinical trials were included, analyzed according to participant diagnosis. Conclusion: The evidence found was heterogeneous, but contributed to elucidating uncertainties regarding the use of nasal lavage in the clinical practice of physical therapy, such as the protocols used.